Komponensial dan Sintagmatik untuk Mengidentifikasi Struktur Kalimat Dalam Surah Luqman - Supu, Firta; Safii, Randi; Cono, Bajik Alhamda; Suleman D Kadir (Faculty of Education and Teacher Training, 2024)
Surah Luqman, the 31st chapter of the Quran, is situated in the 21st juz and comprises 34 verses. This Meccan surah is the focus of our research, which employs a semantic approach (ilm adh-dilalah) to analyze syntagmatic components, particularly in verses 12-15. The study utilizes a literature review methodology, concentrating on componential analysis and syntagmatic relationships between lexical elements. Our objective is to gain a profound understanding of sentence structures, explore meaning relationships among syntagmatic components, and analyze semantic field implications. The research findings demonstrate that applying componential and syntagmatic analyses provides enhanced comprehension of sentence structures and their inherent meaning relationships. The examined verses offer deep insights into the moral messages and practical guidance in Surah Luqman, especially concerning gratitude to Allah, avoiding polytheism, kindness to parents, and performing prayers. This study contributes to the linguistic understanding of sentence structures within a religious context and enriches the interpretation of these verses from a linguistic perspective. By bridging linguistic analysis with Quranic exegesis, this research opens new avenues for interdisciplinary studies in Islamic linguistics and hermeneutics, potentially informing both scholarly discourse and practical application of Quranic teachings.